Fidelity and Effectiveness of a Caregiver Mediated Compliance Training for Children with Autism Spectrum Disorder. Issue 3 (3rd July 2022) - Gunderson, Jaclyn; Symons, Frank; Wolff, Jason
Abstract: Behavioral strategies can effectively improve compliant responses to instructions. However, research on caregivers' fidelity to implement strategies is generally lacking. The current study's purpose was to evaluate caregiver fidelity to a behavioral intervention to increase compliant responding to instructions in children with autism spectrum disorder (ASD). Participants included three children (ages 7–9) and their caregivers. Results showed an overall increase in fidelity and compliant responses with variability in the mastery of different intervention techniques. The results suggest that while caregiver interventions for building compliance are overall effective, monitoring fidelity to specific strategies is necessary for targeted training of caregiver-mediated interventions.